Production of ultra-high concentration calcium alginate beads with prolonged dissolution profile1. Issue 46 (23rd May 2015) - Voo, Wan-Ping; Lee, Boon-Beng; Idris, Ani; Islam, Aminul; Tey, Beng-Ti; Chan, Eng-Seng
<x xml:space="preserve">Abstract</x> Ultra-high concentration (UHC) calcium alginate beads produced by temperature-controlled extrusion-dripping system show prolonged dissolution profile.